2006
DOI: 10.1017/s0012162206000259
|View full text |Cite
|
Sign up to set email alerts
|

Functional independence among young adults with spina bifida, in relation to hydrocephalus and level of lesion

Abstract: Knowledge about the level of functional independence that can be expected in adulthood might support decisions on the treatment of newborn infants with spina bifida. This study determined functional independence among young adults with spina bifida and its relationships with pathological characteristics known from birth (hydrocephalus and level of lesion). Data were collected from medical records and by physical examination. Functional independence was assessed on six domains (self-care, sphincter control, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 22 publications
5
61
2
1
Order By: Relevance
“…Consistent with previous reports of the central role that independence in daily life activities plays in one's capacity for community living, 10 self-management was a significant predictor of living situation. Participants who reported greater selfmanagement skills were more likely to have current residence in unsupervised settings.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous reports of the central role that independence in daily life activities plays in one's capacity for community living, 10 self-management was a significant predictor of living situation. Participants who reported greater selfmanagement skills were more likely to have current residence in unsupervised settings.…”
Section: Discussionsupporting
confidence: 88%
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted.…”
Section: Discussionmentioning
confidence: 74%
“…Children with more than four shunt revisions also have a lower functional level [2,11,12,28]. Transition from childhood to young adulthood can be an especially difficult developmental period for those with MM [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to guide the families so that children acquire the greatest independence possible, considering the scores of each age group. Physical therapy also aims to prevent secondary deformities, decubitus ulcers, and secondary cognitive changes 3,[9][10][11] . Physical therapy should promote the learning of motor skills, postural adjustments, independent locomotion (if necessary, with resources such as crutches or a wheelchair), to ensure the maximum functional independence possible 3,5,9,12 .…”
Section: Resultsmentioning
confidence: 99%